45. Intraoperative neurophysiological monitoring during aortic aneurysm repair: A single center experience and focus on methodological aspects. Issue 12 (December 2017) - Bianchi, F.; Cursi, M.; Amadio, S.; Guerriero, R.; Butera, C.; Tronci, S.; Caravati, H.; Melissano, G.; Chiesa, R.; Comi, G.; Del Carro, U.
Abstract : This study describes our experience with neuromonitoring in thoracoabdominal aortic aneurysms (TAAA) repair, focusing on the set up of a monitoring protocol, aimed to optimize the detection of spinal cord ischemia. A retrospective observational study was carried out on 62 consecutive patients (37 men; mean age 63.8 years) undergoing TAAA repair between February 2016 and March 2017. All patients underwent Motor Evoked Potentials (MEPs), Somatosensory Evoked Potentials (SSEPs), neurophysiological monitoring of peripheral ischemia, and continuous control of other intraoperative variables. The mortality rate was 9.6%, and the incidence of immediate and delayed neurological deficits was 6.4% and 3.2% respectively. Significant MEP changes occurred in 41.6% of patients, recovering in 85% of cases. Permanent MEPs changes occurred in 3 patients (15%), 2 of them developed immediate paraplegia. Significant SSEPs changes occurred in 6 patients (12.2%) and recovered in all but one, awaking with paraplegia. False negative and positive rate were both 1.6%. Our data are consistent with the literature. However, a consensus is still lacking with regard to an intraoperative protocol for monitoring, which limits the comparison of different studies. Our method demonstrated a good reliability and could contribute to the setup of a consensus protocol.